At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
Okay, so suppose we have the form: "All p must be q". The question is does this mean \(p\implies q\) or \(q \implies p\)? You have to test it out a bit.
So I'd start out with something like... "All dogs must be animals". Now does this mean "If you're a dog, then you're an animal." or does it mean "If you're an animal, you must be a dog"?
@princesspixie Does this help?
a little but what does a dis junction mean?
Disjuntion isn't mentioned, but I'd assume it's two propositions combined with 'or'.
oh i meant to say conjunction sorry!
conjunction is when you take two propositions and combine them with and or or.
but the sentence already has the word and in it so thats why im confused..
Which just means you use and \( \wedge\) for it.
can you give me an example..
this would be the first answer ? : “All mathematicians must be good logicians ^ good logicians must justify their claims.”
No, because you need to convert them into conditionals.
“if you are a mathematicians then you must be a good logician and all good logicians must justify their claims.” ??
Yeah, now I'd say that \(p\) means 'person is mathematician' \(q\) means 'person is good logician' and \(r\) means 'justifies their claims'
So we end up with \[ (p \implies q)\wedge(q \implies r) \]
ok, is that part of the answer?
That is part a.
ok, great thanks! how would i negate it now? just throw a not in front of the original sentence?
Yeah, throw in a \( \lnot \) .
and you may have to simplify
\( \neg ( ( p \implies q ) \wedge ( q \implies r ) ) \) \( \neg ( p \implies q ) \vee \neg ( q \implies r ) \) \( (p \wedge \neg q) \vee (q \wedge \neg r) \)
which means, the statement is true, whenever a 'mathematician is not a logician' or whenever a 'logician is not a justfier'
which forms a logical negation of the original statement
ok thank you :)
np.. yw :)
so should the negation be : a mathematician is not a good logicians and logicians do not justify claims ?
needs to be an or in the middle
so would it be : a mathematician is not a good logician or logicians would justify their claims?